The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1600-051x.2010.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of toothbrushing to reduce ventilator-associated pneumonia pathogens and dental plaque in a critical care unit

Abstract: Powered toothbrushes are highly effective for plaque removal in intubated patients in a critical unit and should be tested for their potential to reduce VAP incidence and health complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 22 publications
(28 reference statements)
1
37
1
3
Order By: Relevance
“…For example, there could be cases where plaque indices differ not as a result of changes in bacterial number, but due to the relative quantity of EPS. This result is in contrast to the study of Needleman et al 43 where chlorhexidine in combination with a toothbrush or foam swab led to significant reductions in the number of plaque bacteria recovered.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…For example, there could be cases where plaque indices differ not as a result of changes in bacterial number, but due to the relative quantity of EPS. This result is in contrast to the study of Needleman et al 43 where chlorhexidine in combination with a toothbrush or foam swab led to significant reductions in the number of plaque bacteria recovered.…”
Section: Discussioncontrasting
confidence: 99%
“…Needleman et al compared a powered toothbrush with a foam swab in 46 individually randomised patients, with cleaning undertaken four times a day for 2 min in combination with 20 mL of 0.2% chlorhexidine. The study found that a powered toothbrush was significantly better at reducing plaque 43. However, it was also observed that foam swabs reduced plaque scores significantly from baseline.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…One report was translated from Spanish to English to evaluate eligibility (37). Of 14 potentially eligible studies, we excluded one Low risk of bias High study of toothbrushing which did not randomize patients (45); two studies that started as randomized trials but which became observationalstudies following low enrolment (46) or apparently large treatment effect (47), neither of which reported numerators or denominators; two trials that reported dental plaque but not VAP and that focused on the outcome of intracranial pressure (48,49); and three trials using toothbrushing as part of a standard oral care protocol in both groups testing chlorhexidine vs. control (50,51) or chlorhexidine vs. bicarbonate vs. control (52). Agreement on trial selection was 100%.…”
Section: Trial Identificationmentioning
confidence: 99%
“…Also, correct oral hygiene with tooth-brushing and oral decontamination with antiseptics (chlorhexidine and triclosan rinses on plaque, gingivitis, supragingival calculus and extrinsic staining) [14] has proven to be effective in reducing the incidence of ventilatorassociated pneumonia [15][16][17][18]. However, the role of poor oral hygiene and oropharyngeal bacterial colonization by potential respiratory pathogens on the development of community-acquired pneumonia (CAP) remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%